Disease outbreak management : Hospital administrator's perspective - Kumar Gupta,Shakti; Kant, Sunil; Kumar SharmaNeN, Jitendra (New Delhi: JAYPEE, 2013)
Proporciona un plan de acción integral y tendencias recientes en el manejo de brotes de enfermedades. Recomienda elementos administrativos esenciales para la gestión de brotes de enfermedades a nivel local, nacional e internacional. incorpora una lista de verificación para evaluar el estado de preparación y facilitar el desarrollo de capacidades para la gestión de brotes de enfermedades. Analiza temas como el pronóstico de epidemias, la inteligencia epidémica y las regulaciones nacionales e internacionales relacionadas con las epidemias. Un complemento invaluable para los administradores, gerentes, profesionales de la gestión clínica, ejecutivos médicos y responsables de políticas en el suministro de atención médica de hospitales y atención médica.
Contenido Disease Outbreak Management: An Overview Definitions Classification of Outbreaks 2. Role of Healthcare Institutions When and How to Respond? Disease Outbreak Management Plan Hospital Infection Control Team Outbreak Control Team Important Processes and Facilities Epidemic Forecasting Epidemic Intelligence 3. Responsibilities of Hospital Administrators Team Work Special Facilities Standardization Laboratory Services Inventory Management Security of Stores Budget Staff Health Safety Sterilization Procedures Blood Bank Networking Biomedical Waste Management Reporting Media Management Ambulance Services Research Preservation of Samples/Specimen Outreach Camps Initial Assessment Pharmacovigilance Documentation of Outbreaks and Investigations Coordination Recent Trends Designing Isolation Facilities Specific for Infectious Diseases Disease Outbreaks and International Health Regulations 4. Rating the Preparedness Checklist Glossary Appendices Appendix 'A': The Notifiable Diseases as Applicable to Greater Mumbai Appendix 'B': The Notifiable Diseases in 2011 as per CDC Atlanta Appendix 'C': National Surveillance Programme for Communicable Diseases Appendix 'D': The Epidemic Diseases Act Bibliography Index
Incluye índice general
Incluye índice temático
Incluye bibliografía
Keywords: ENFERMEDADES OPORTUNISTAS; INFECCIONES NOSOCOMIALES; HOSPITALES -- ADMINISTRACIÓN